2021
DOI: 10.3389/fcvm.2021.682027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translation of Three-Dimensional Scar, Diffusion Tensor Imaging, Four-Dimensional Flow, and Quantitative Perfusion in Cardiac MRI: A Comprehensive Review

Abstract: Cardiovascular magnetic resonance (CMR) imaging is a versatile tool that has established itself as the reference method for functional assessment and tissue characterisation. CMR helps to diagnose, monitor disease course and sub-phenotype disease states. Several emerging CMR methods have the potential to offer a personalised medicine approach to treatment. CMR tissue characterisation is used to assess myocardial oedema, inflammation or thrombus in various disease conditions. CMR derived scar maps have the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 149 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…The benefits of imaging with better contrasts, SNR and resolution at 5T are yet to be demonstrated with a larger patient cohort with cardiovascular diseases. Second, this work only focused on CINE imaging, and other CMR techniques such as tissue characterization ( 29 ) and quantitative mapping ( 30 , 31 ), should be further evaluated in future works. Third, only a normal flexible body coil was currently available on the 5T system, while further improvement in imaging quality can be expected with dedicated cardiac coils ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of imaging with better contrasts, SNR and resolution at 5T are yet to be demonstrated with a larger patient cohort with cardiovascular diseases. Second, this work only focused on CINE imaging, and other CMR techniques such as tissue characterization ( 29 ) and quantitative mapping ( 30 , 31 ), should be further evaluated in future works. Third, only a normal flexible body coil was currently available on the 5T system, while further improvement in imaging quality can be expected with dedicated cardiac coils ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac fibrosis after myocardial infarction is one of the common clinical types of myocardial fibrosis, and the core pathology is that the main effector cells of myocardial fibrosis after myocardial infarction are induced by pro‐fibrotic factors such as oxidative stress and inflammatory factors, which leads to changes in biological behaviors such as proliferation, phenotypic differentiation, migration, and secretion, resulting in massive deposition of extracellular matrix, cardiac remodeling, and fibrosis, affecting cardiac diastolic function and electrical signal. It also leads to heart failure and arrhythmias, and affects prognosis 25,26 . ST2 has been demonstrated as a marker of myocardial fibrosis 27 .…”
Section: Discussionmentioning
confidence: 99%
“…23 AST is found in large numbers in the heart muscle cells and liver. When the supplement of blood is reduced, a large amount 25,26 ST2 has been demonstrated as a marker of myocardial fibrosis. 27 In the present study, we found that serum ST2 levels were positively correlated with ALT, AST, and BNP in the control population, and that ST2 levels were negatively correlated with HGB and TG in USAP patients, while ST2 levels were positively correlated with WBC, GLU, and BNP in NSTEMI patients, which suggested an interrelationship between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that DTI is a technology based on DWI to quantify the anisotropy of water molecules and measure the degree and direction of water molecule diffusion[ 61 ]. DTI is expected to analyse the data of water molecular diffusion in three-dimensional space to noninvasively observe the damage severity of myocardial tissue infected by SARS-CoV-2 and evaluate whether the myocardial structure integrity has been lost[ 62 ]. Clinicians should be vigilant against the possible late-onset effects of convalescent patients with COVID-19 and use the CMR multiparameter model to dynamically and quantitatively evaluate myocardial fibrosis in follow-up.…”
Section: Covid-19 Related Myocarditismentioning
confidence: 99%